INPUT, PROSES, OUTPUT PEMBUATAN MUSIK BUMPER: PADA PROGRAM ACARA KUIS PAKIS BALI DI BALI TV - Luthfiansyah, Muhammad Raihan Luthfiansyah; Wiyati, Wahyu Sri; Ardini, Ni Wayan (UPT Pusat Penerbitan LP2MPP ISI Denpasar, 2024)
Bumper is an opening animation in a television program, serving as a short animation to depict the identity of a show or institution. Every TV program typically features a bumper to showcase its identity. During the internship in the MBKM 2023 program at Bali TV, I had the opportunity to create bumper music for the quiz show